2018
DOI: 10.1002/cbic.201800367
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the ACT Domains and Catalytic Subunits of Acetohydroxyacid Synthases (AHASs) from Different Species

Abstract: Acetohydroxyacid synthase (AHAS), which catalyzes the first step in the biosynthesis of branched-chain amino acids, is a target of several types of potent herbicides and antimicrobials. AHAS contains the catalytic subunit (CS) and the regulatory subunit (RS). The AHAS RS is usually composed of ACT domains and C-terminal domains. Herein, it is reported that the ACT domain of AHAS RS from different species could efficiently activate its respective CS. Moreover, the universal cross-activation between the CSs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…The CSs from plants and fungi already had certain enzyme activities that were comparable to that of Ec CSI. These relative activities for AHASs are consistent with our previous report and were determined by the A 525 method. We also chose a plant At CS to study in detail via the fluorogenic assay and found that the fluorescence changes were similar to that for Ec CSI (Figure S11), and the binding constants for probe 1 , ThDP, and FAD could be obtained from the fluorogenic assay as 87.0, 4.2, and 0.23 μM, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The CSs from plants and fungi already had certain enzyme activities that were comparable to that of Ec CSI. These relative activities for AHASs are consistent with our previous report and were determined by the A 525 method. We also chose a plant At CS to study in detail via the fluorogenic assay and found that the fluorescence changes were similar to that for Ec CSI (Figure S11), and the binding constants for probe 1 , ThDP, and FAD could be obtained from the fluorogenic assay as 87.0, 4.2, and 0.23 μM, respectively.…”
Section: Resultssupporting
confidence: 91%
“…Using solution NMR studies, our group had shown that IlvN interacts with the α and β domains of IlvB . These studies have been supported by recent biophysical and mutagenesis studies of the RSU–CSU interactions of E. coli AHASs . Thus, the CSU–RSU interaction is proposed to occur at the α–β interface on IlvB, with the residues on IlvN described above being the region of contact.…”
Section: Discussionmentioning
confidence: 99%